Technological Inclusivity and Equity for Students with Visual Impairments in Ghanaian Teacher Education: Examining the Role of Assistive Technologies - Gidisu, Prosper; Abroampa, Winston Kwame; Nyatsikor, Maxwell Kwesi Graves (Indonesian Journal of Education and Social Sciences, 2026)
This study examines the impact of access to assistive technologies (AAT) on inclusive practices for equitable educational experiences (IPEEE) for students with visual impairments (SVIs) in colleges of education (CoEs). A mixed-methods approach utilising a convergent parallel research design was implemented. Data were gathered from 20 SVIs within three special needs-designated CoEs. Data were collected using a self-administered structured questionnaire that utilised a four-point Likert-type scale.  The analysis employed Pearson's correlation, utilising IBM SPSS version 27. The Pearson correlation analysis indicated a weak positive relationship between AAT and IPEEE (r = 0.236, p = 0.317). This suggests that while access to assistive technologies may enhance inclusive practices, it is insufficient to ensure equitable educational experiences for SVIs. The findings underscore the need for a holistic approach that integrates institutional support, pedagogical inclusion, and systemic enhancements in technology utilisation. The research underscores the necessity of addressing systemic and attitudinal barriers to achieve comprehensive and inclusive education.